Two new species of the bamboo-feeding subgenus Myittana (Benglebra) from China (Hemiptera: Cicadellidae: Deltocephalinae) - Luo, Qiang; Yang, Lin; Chen, Xiang-Sheng (Zootaxa, 2019)
Two new leafhopper species of the bamboo-feeding subgenus Myittana (Benglebra), M. (Benglebra) biflaka sp. nov. and M. (Benglebra) curvata sp. nov. are described and illustrated from the southwest of China (Yunnan Province). A new combination, M. (Benglebra) ventrospina (Chen & Yang, 2007), comb. nov. is proposed. Female genitalia of four Chinese species are described and illustrated for the first time. A key to all known species is also provided.